Journalists and the development of a culture of frontier. Strategies for binational integration - Portugal de Rodrich, María Luisa (2022)
n august of 2000, a group of professor from the Universidad de Piura (University of Piura) had the great satisfaction of being selected to participate in the First Citizen Diplomacy and Conflict Solving Workshop (I Taller de Diplomacia Ciudadana y Resuloción de Conflictos),in the city of Cuenca (Ecuador).   Bout twenty university professors, Ecuadorian and Peruvian, from various academic disciplines, gathered with the aim of taking advantage of the opportunity which was offered by the recent signing of the peace agreement between the two nations and of beginning to build different type of coexistence.   Under the leadership of Saul Sosnowski and Edy Kauffman, representatives from the Maryland Group, specialists in cultural mediation and conflict solving, and the sponsorships of AUSENP Associación de Universidades del Sur de Ecuador y Norte del Perú (Southern Ecuador and Northern Perú Universities Association), during five long days of intense work we made efforts to find ways and mechanisms which each one of the participants -in accordance with their field of expertise- could put into practice upon arriving to their place of origin.